Rancang Bangun Website Company Profile Berbasis NextJs dan RAD (Studi Kasus: Dinas Lingkungan Hidup Majalengka) - Rochmat, Saeful; Prasetyo, Tri Ferga (Universitas Majalengka, 2025)
This study aims to develop a prototype of a company profile website for the Environmental Agency Dinas Lingkungan Hidup (DLH) of Majalengka Regency as an initial step to support public information transparency and service digitalization. Currently, DLH Majalengka does not have an official website, which makes it difficult for the public to access information regarding environmental data, waste management, or complaint services. To address this issue, the research adopts the Rapid Application Development (RAD) method, which emphasizes fast development and user involvement in every stage. The research process includes requirements planning, system design using wireframes and UML diagrams, system development with the NextJS framework supported by TailwindCSS and Prisma ORM, and testing using blackbox feature testing. The results indicate that the prototype website has met the agency’s basic needs, including presenting organizational profiles, structure, environmental data publications, public complaint services, and an admin dashboard for report management. Significantly, this research contributes to strengthening e-government practices at the regional level, improving institutional transparency, and creating opportunities for further system development. The prototype has great potential to be officially implemented and to serve as a reference for developing government websites in other regions of Indonesia.